Plantarhyperhidrosis: The Efficacy Of Iontophoresis With Tap Water, Glycopyrronium Bromide And Indomethacin: Life Sciences-Physiotherapy for better pain management - Dr.C.V.Senthilnathan1; G.Vaishnavi; G.Keerthana; S.NandhaKumar; Dr.Kotteeswaran (International Journal of Life Science and Pharma Research, 2022)
Hyperhidrosis is an excessive production of sweat more than the physiological amount necessary to maintain thermal homeostasis. Primary focal hyperhidrosis is a disorder of unknown etiology, causing excessive, bilateral, symmetrical sweating on the soles of the foot is called plantar hyperhidrosis. The condition results not only in physical impairment, but also interferes with professional and social life. Although not life- threatening, it is very uncomfortable and cause embarrassment and psychological trauma. Iontophoresis is a helpful method, which includes the presentation of particles into the body tissue through the skin. The essential principle is to place the ion particles under an electrode with the same charge, i.e. negative ion placed under cathode and positive ion placed under anode. This complete process is also known as “technique of ion transfer” into the body tissues by using electrical current as a driving force. It is a comparative study with pre and post intervention. 30 subjects with plantar hyperhidrosis were selected based on the inclusion criteria. The study duration was for about 4 weeks30 subjects of age group between 15 –25 years with idiopathic plantar hyperhidrosis of both male and female subjects were included in this study. Subjects with cardiac and respiratory disorders, pregnant or lactating, any cuts, abrasions, eczema or infections on plantar aspect, metal implants like pacemakers, Hypersensitivity to the active substance were excluded. The subjects were divided into 3 group Group A treated with iontophoresis using tap water alone. Group B were treated with iontophoresis using tap water along with 3%-5% of anticholinergic drug, glycopyrronium bromide solution. Group C were treated with iontophoresis using tap water along with 1% of indomethacin (NSAID). The result of this study shows that there were significant changes in outcome measures. On comparing Mean values of Group A, Group B & Group C on Minor test (Starch - Iodine Test) tap Water along with Glycopyrronium Bromide (Group B) shows 1.60 which has the Lower Mean value is effective than Group A and Group C .On comparing Mean values of Group A, Group B & Group C on Visual Analog Scale score tap Water along with Glycopyrronium Bromide (Group B) shows 3.80 which has the Lower Mean value is effective than Group A and Group C. On comparing Mean values of Group A, Group B & Group C on Hyperhidrosis Disease Severity Scale tap Water along with Glycopyrronium Bromide (Group B) shows 1.40 which has the Lower Mean value is effective than Group A and Group C. On comparing all the three groups, Group B shows better result than Group C and Group A in outcome measure. This study concluded that Tap water along with glycopyrronium bromide reduces the excessive sweating and decrease the sweating symptoms in subjects with plantar hyperhidrosis.